2018
DOI: 10.1159/000492231
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Anesthesia Precludes LFP-Based Functional Mapping of Pallidum during DBS Implantation

Abstract: Background/Aims: There are reports that microelectrode recording (MER) can be performed under certain anesthetized conditions for functional confirmation of the optimal deep brain stimulation (DBS) target. However, it is generally accepted that anesthesia affects MER. Due to a potential role of local field potentials (LFPs) in DBS functional mapping, we characterized the effect of propofol on globus pallidus interna (GPi) and externa (GPe) LFPs in Parkinson disease (PD) patients. Methods: We collected LFPs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…However, the exact degree of the effect remains unclear. Nevertheless, the mean frequency and other electrophysiological properties, such as local field potentials [ 32 , 33 ], are modified by anesthesia. Therefore, it is reasonable to identify lower values of frequency discharge in anaesthetized versus awake patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact degree of the effect remains unclear. Nevertheless, the mean frequency and other electrophysiological properties, such as local field potentials [ 32 , 33 ], are modified by anesthesia. Therefore, it is reasonable to identify lower values of frequency discharge in anaesthetized versus awake patients.…”
Section: Discussionmentioning
confidence: 99%
“…From a methodological viewpoint, it is important to consider that all patients were under general anesthesia, and this condition can modify neuronal discharge features and perhaps the synaptic functions of some thalamic nuclei [32], but the exact degree of the effect remains to be elucidated. However, it is known that the mean frequency discharge (a useful variable during MERs) [16,17,18,33] and other electrophysiological properties, such as local field potentials [34], are affected by anesthesia. However, there is evidence in a study of DBS of the subthalamic nucleus (STN) that localization with MER and patient comfort can be achieved with equal effectiveness in patients under generalized anesthesia compared with that in awake patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…General anesthesia is widely accepted to be associated with a decreased neuronal spiking rate in the STN of DBS patients, although this has been debated [129,130]. LFP appear to be more susceptible to anesthesia, as a recent study by Malekmouhammadi et al has demonstrated diminished relative power differences in beta oscillation and high-frequency oscillation in LFP recorded from the GPi of asleep patients compared to awake patients [131]. Authors reported that the differences in LFP between the GPe and GPi were all but obliterated under general anesthesia, severely limiting the potential of LFP as an aid in intraoperative targeting [131].…”
Section: Clinical Application: Use Of Electrophysiology During Aslmentioning
confidence: 99%